Effect of season on anti-oxidative enzymatic status and lipid peroxidation of murrah buffalo semen (Indian Journal of Animal Production and Management, 2018)
Present study was conducted to examine the effect of different seasons on anti-oxidative enzymatic status  and lipid peroxidation of Murrah buffalo semen. Semen of six breeding Murrah bulls was collected twice  a week using AV method for one complete year. A total of 144 semen samples were collected in entire  experiment. Seminal plasma was separated and stored at –20°C. Malondialdehyde (MDA) concentration was  estimated in fresh semen samples, while total anti-oxidant capacity (TAC) and superoxide dismutase (SOD)  activities were determined in seminal plasma by spectrophotometry. The MDA concentration was found  to be significantly (p < 0.01) different in different seasons. Minimum concentration of MDA was observed  during winter season. Concentration of TAC was significantly (p
Keywords: Enzyme; Lipid; Peroxidation; Season